STRATEGI PENGEMBANGAN USAHA SEKTOR WELLNESS TOURISM PADA AYU SPA BALI: Indonesia - Ariarta, Putu Agus Yoga Brahmanda; Angga Guntara, Alpin; Yasa, Ni Nyoman Kerti (PT Naureen Digital Education, 2023)
This research aims to identify the opportunities, threats, strengths, and weaknesses of Ayu Spa Bali in Badung Regency, Bali. The results of this identification will be used as the basis for developing business development strategies. The approach used in this research is the SWOT Analysis and Internal- External Matrix. The research findings indicate that Ayu Spa Bali has strong strengths and favorable opportunities in its effort to expand its business. Based on the existing environmental conditions, Ayu Spa Bali is positioned in the Growth stage (concentric diversification). Therefore, the suitable business strategy to be developed is the concentric diversification strategy, with a focus on product diversification, differentiation, product branding, and maximizing collaborations with professionals